Factores de riesgo de complicaciones hemodinámicas después de la administración de la anestesia raquídea en gestantes cesareadas del Hospital Regional Docente de Trujillo - Cárdenas Villafuerte, Eduardo Franco (2020)
Caesarean section is performed in 30% of births and is the most common surgical procedure in the United States. In Peru, the cesarean section rate has remained around 21% in the public sector, in the private sector rates have accelerated since the beginning of this decade, going from 28.6% in the period 1991-1993 to 48, 6% in the period 2002-2005. In the 2002-2005 period, the cesarean section rate was 43% for women without insurance and 69% for women who had private health insurance. Regional anesthesia techniques are currently the most used for cesarean section, and are used even in situations that were previously considered an indication for general anesthesia (cord prolapse, preeclampsia, placenta previa). Although the caesarean section rate has remained constant (23.1-30%), the use of general anesthesia has greatly decreased (0.8% of all caesarean sections). Arterial hypotension is the most frequent complication of spinal anesthesia in pregnant women and can be potentially dangerous for both the mother and the fetus. Its incidence in C-sections has been reported from 40-50% to 100% when preventive measures are not used. Decreases in systolic blood pressure lower than 100 mmHg, or those that exceed 20% of the baseline value, are associated with risk of placental hypoperfusion and, when these changes are maintained for more than 2 min, they may involve a compromise of fetal well-being. Factors that contribute to greater arterial hypotension: The small stature the length of the spine allows a high anesthetic level, the advanced age, as the age increases the volume of the spinal and epidural space becomes smaller, so these patients develop greater spread cephalic of the local anesthetic. Obesity, this state develops greater supine hypotension and sympathetic activity, and also further accentuates aorto-cava compression, decreases subarachnoid space and cerebrospinal fluid pressure, all due to the important fat deposit in these regions that also increases pressure intra-abdominal with more cephalic displacement of the spinal block